Penerapan Media Pembelajaran Slow Motion Terhadap Hasil Belajar Roll Depan - Febriyanti, Irma (Indonesian Journal of Physical Education and Sport Science, 2023)
Study Purpose. The use of learning media has a role in the learning process. The use of appropriate media can improve student learning achievement. This study aimed to determine the effect of slow-motion learning media on forward-roll learning achievement. Materials and methods. This research was a quantitative descriptive research in the form of a quasi-experimental. The population in this study was all classes of V at SDN Balonggabus with the sample used, namely 31 students. This research was conducted 4 times. The data collection technique used was the learning achievement test instrument. The analysis technique used was descriptive, normality test, and hypothesis testing to prove the influence of learning media on student learning achievement. Results. Based on the analysis results, the results showed that there was influence as evidenced by the hypothesis test results of 0.00, which means <0.05. Conclussion. Concluded that there was a significant influence of the application of slow-motion learning media on learning achievement of forward roll.